Tapajos cristinae gen. n., sp. n. (Diptera: Chironomidae: Chironominae) from the Neotropical region - Trivinho-Strixino, Susana; Da Silva, Fabio Laurindo; de Oliveira, Caroline Silva Neubern (Zootaxa, 2013)
A new genus of non-biting midges, Tapajos gen. n., is erected for T. cristinae sp. n. from the Neotropical region, and placed in the subfamily Chironominae, tribe Chironomini. Adult males are characterized by the combination of bare eyes; antenna with 11 flagellomeres; antepronotal lobes fused medially; fore tibia with inner scale broad and rounded; superior volsella with a long sickle shaped, bare part arising from the distal lateral corner of a globose, densely trichiose base; inferior volsella sub-cylindrical, surpassing the anal point, distally setose and slightly expanded.